Description of a new species of the genus Eryngiopus Summers (Acari: Stigmaeidae) from Turkey - Dogan, Salih; Dilkaraoglu, Sibel; Fan, Qing-Hai; Erman, Orhan; Sevsay, Sevgi; Adil, Sezai (Systematic & Applied Acarology Soc London, Natural History Museum, 2015)
A new species of the genus Eryngiopus Summers, Eryngiopus anatolicus sp. nov. collected from litter under Astragalus sp. from Turkey is described and illustrated.
Keywords: Raphignathoid Mites; Iran; Prostigmata; Checklist; Citrus; Usa